PENGARUH MOTIVASI KERIA TBRHADAP KINERIA GURU PADA SMA NEGERI DI WONOGIRI - , Tinuk Triyana ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to examine the effect of job motivation in the form of achievement motivation, affiliation motivation and power motivation on the performance of teachers in state high schools in Wonogiri. This study is a survey research using a sample of 100 respondents that are randomly selected from the population of twelve (12) state high schools in Wonogiri. The data are collected through a questionnaire, while data analysis techniques use Multiple Regression Analysis. The results of this study shows that achievement motivation has a positive and significant impact on teacher performance. Motivation of affiliation has positive and significant influence on teacher performance. Likewise with motivation of power also shows positive and significant effect on the performance of teachers. Furthermore, both variables simultaneously have an influence on the performance of teachers.